VAN DER WAALS MIXING RULES FOR THE REDLICH-KWONG EQUATION OF STATE. APPLICATION FOR SUPERCRITICAL SOLUBILITY MODELING - Ratnawati Ratnawati (Dept. of Chemical Engineering, Diponegoro University, 2006)
A solid-supercritical fluid system is highly asymmetric in terms of the size and energy differences of the components. The key point in extending a cubic equation of state to such system is on the choice of proper mixing rules. New mixing rules for the Redlich-Kwong equation of state are developed. The developement is based on the statistical-mechanical theory of the van der Waals mixing rules. The Redlich Kwong equation of state with the proposed mixing rules along with the original ones is used to predict solubilities of solids in supercritical fluid. The prediction is done with kij equal zero, as well as with optimized kij. The results show superiority of the proposed mixing rules over the original ones. For most of the systems considered, the proposed mixing rules with the kij equal zero are closer to the experimental data than the original ones do. For 28 systems with 521 data points taken from various sources, the original and the proposed mixing rules give the overall AAD of 13.4%, while the original mixing rules give 45.9%.